(untitled) (Journal of Atomic, Molecular, Condensed Matter and Nano Physics, 2020)
We have reported fine structure energies along with radiative data namely, transition wavelengths, transition probabilities, oscillator strengths and line strengths for lowest 120 levels of Cu-like W using Multi-Configuration Dirac-Fock (MCDF) method which may be useful ion for fusion plasma research. We have systematically analysed configuration interaction (CI) effects on Dirac-Coulomb as well as Breit and Quantum electrodynamics (QED) excitation energies and demonstrated that in order to attain accuracy in atomic data inclusions of CI in excitation energies are crucial. We have also discussed the evaluation of results from two independent codes GRASP and FAC. We have predicted some new energy levels and transition data where no other experimental or theoretical results are available. The present set of results should be useful in line identification and the interpretation of spectra, as well as in modeling of fusion plasmas.